2017
DOI: 10.12707/riv17017
|View full text |Cite
|
Sign up to set email alerts
|

Stress and stressors in bus drivers

Abstract: Background: Occupational stress is one of the main pathological disorders triggered by inadequate processes at work. Objectives: To investigate stress and stressors in bus drivers. Methodology: A descriptive, exploratory study with a quantitative approach was conducted with 321 bus drivers, using Lipp's Inventory of Stress Symptoms for Adults. The chi-squared test, the Fisher's exact test, and the Likelihood-ratio test (CI = 95%) were applied. Results: In this sample, 75.6% of the stressed bus drivers are in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
0
0
1
Order By: Relevance
“…A British researcher (6) showed that these conditions including peak traffic conditions were correlated with the increase of stress hormones during driving, which may be injurious to an individual's mental wellbeing. A Brazilian study showed that bus drivers had various job stress stages, while 75.6% of the participants were in the exhaustion stage of stress (7). Studies in Asia had similarly pointed out the injurious nature of occupational stress among bus drivers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A British researcher (6) showed that these conditions including peak traffic conditions were correlated with the increase of stress hormones during driving, which may be injurious to an individual's mental wellbeing. A Brazilian study showed that bus drivers had various job stress stages, while 75.6% of the participants were in the exhaustion stage of stress (7). Studies in Asia had similarly pointed out the injurious nature of occupational stress among bus drivers.…”
Section: Introductionmentioning
confidence: 99%
“…A Sri Lankan study showed the prevalence of occupational stress among bus drivers in Maharagama Municipal Council area of 34.1% (95% CI: 29.6, 38.8) ( 9). This study too pointed out that job strain can lead to unhealthy behaviors such as tobacco smoking and dietary habits (6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, este estudo tem como objetivo compreender a percepção dos motoristas de ônibus quanto à sua vivência no trabalho e aos impactos sofridos pelos seus corpos. Além disso, pretende-se demonstrar que a inserção do enfermeiro do trabalho pode contribuir para ações preventivas e para melhoria da saúde mental desses trabalhadores, já que esta influencia diretamente o estado emocional do sujeito (12).…”
Section: Introductionunclassified